Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's start by differentiating each function with respect to [tex]\( x \)[/tex] step-by-step.
### Problem 6: Differentiate [tex]\(\left(4 x^2 - 7 x + 5\right) \cdot \sec x\)[/tex]
Given the function:
[tex]\[ f(x) = \left(4 x^2 - 7 x + 5\right) \cdot \sec x \][/tex]
To differentiate the product of two functions, we use the product rule:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Let:
[tex]\[ u = 4 x^2 - 7 x + 5 \][/tex]
[tex]\[ v = \sec x \][/tex]
Now, find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx}(4 x^2 - 7 x + 5) = 8 x - 7 \][/tex]
[tex]\[ v' = \frac{d}{dx}(\sec x) = \sec x \tan x \][/tex]
Applying the product rule:
[tex]\[ f'(x) = u'v + uv' \][/tex]
[tex]\[ f'(x) = (8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x \][/tex]
So the derivative is:
[tex]\[ f'(x) = (8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x \][/tex]
### Problem 7: Differentiate [tex]\( x^4(5 \sin x - 3 \cos x) \)[/tex]
Given the function:
[tex]\[ g(x) = x^4 (5 \sin x - 3 \cos x) \][/tex]
Again, use the product rule:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Let:
[tex]\[ u = x^4 \][/tex]
[tex]\[ v = 5 \sin x - 3 \cos x \][/tex]
Find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx}(x^4) = 4 x^3 \][/tex]
[tex]\[ v' = \frac{d}{dx}(5 \sin x - 3 \cos x) = 5 \cos x + 3 \sin x \][/tex]
Applying the product rule:
[tex]\[ g'(x) = u'v + uv' \][/tex]
[tex]\[ g'(x) = 4 x^3 (5 \sin x - 3 \cos x) + x^4 (5 \cos x + 3 \sin x) \][/tex]
Simplify:
[tex]\[ g'(x) = 4 x^3 (5 \sin x - 3 \cos x) + x^4 (5 \cos x + 3 \sin x) \][/tex]
### Problem 8: Differentiate [tex]\(\frac{\sqrt{x} + 1}{\sqrt{x} - 1}\)[/tex]
Given the function:
[tex]\[ h(x) = \frac{\sqrt{x} + 1}{\sqrt{x} - 1}\][/tex]
To differentiate the quotient of two functions, we use the quotient rule:
[tex]\[ \left( \frac{u}{v} \right)' = \frac{u'v - uv'}{v^2} \][/tex]
Let:
[tex]\[ u = \sqrt{x} + 1 \][/tex]
[tex]\[ v = \sqrt{x} - 1 \][/tex]
Find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx} (\sqrt{x} + 1) = \frac{1}{2\sqrt{x}} \][/tex]
[tex]\[ v' = \frac{d}{dx} (\sqrt{x} - 1) = \frac{1}{2\sqrt{x}} \][/tex]
Applying the quotient rule:
[tex]\[ h'(x) = \frac{u'v - uv'}{v^2} \][/tex]
[tex]\[ h'(x) = \frac{\left(\frac{1}{2\sqrt{x}}\right)(\sqrt{x} - 1) - (\sqrt{x} + 1)\left(\frac{1}{2\sqrt{x}}\right)}{(\sqrt{x} - 1)^2} \][/tex]
Simplify:
[tex]\[ h'(x) = \frac{\frac{\sqrt{x} - 1 - \sqrt{x} - 1}{2\sqrt{x}}}{(\sqrt{x} - 1)^2} \][/tex]
[tex]\[ h'(x) = \frac{-2}{2\sqrt{x} (\sqrt{x} - 1)^2} \][/tex]
[tex]\[ h'(x) = \frac{-1}{\sqrt{x} (\sqrt{x} - 1)^2} \][/tex]
So the final derivative is:
[tex]\[ h'(x) = \frac{1}{2\sqrt{x}(\sqrt{x} - 1)} - \frac{\sqrt{x} + 1}{2\sqrt{x}(\sqrt{x} - 1)^2} \][/tex]
Thus, we have:
1. [tex]\((8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x\)[/tex]
2. [tex]\(x^4 (3 \sin x + 5 \cos x) + 4 x^3 (5 \sin x - 3 \cos x)\)[/tex]
3. [tex]\(\frac{1}{2 \sqrt{x} (\sqrt{x} - 1)} - \frac{\sqrt{x} + 1}{2 \sqrt{x} (\sqrt{x} - 1)^2}\)[/tex]
### Problem 6: Differentiate [tex]\(\left(4 x^2 - 7 x + 5\right) \cdot \sec x\)[/tex]
Given the function:
[tex]\[ f(x) = \left(4 x^2 - 7 x + 5\right) \cdot \sec x \][/tex]
To differentiate the product of two functions, we use the product rule:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Let:
[tex]\[ u = 4 x^2 - 7 x + 5 \][/tex]
[tex]\[ v = \sec x \][/tex]
Now, find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx}(4 x^2 - 7 x + 5) = 8 x - 7 \][/tex]
[tex]\[ v' = \frac{d}{dx}(\sec x) = \sec x \tan x \][/tex]
Applying the product rule:
[tex]\[ f'(x) = u'v + uv' \][/tex]
[tex]\[ f'(x) = (8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x \][/tex]
So the derivative is:
[tex]\[ f'(x) = (8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x \][/tex]
### Problem 7: Differentiate [tex]\( x^4(5 \sin x - 3 \cos x) \)[/tex]
Given the function:
[tex]\[ g(x) = x^4 (5 \sin x - 3 \cos x) \][/tex]
Again, use the product rule:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Let:
[tex]\[ u = x^4 \][/tex]
[tex]\[ v = 5 \sin x - 3 \cos x \][/tex]
Find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx}(x^4) = 4 x^3 \][/tex]
[tex]\[ v' = \frac{d}{dx}(5 \sin x - 3 \cos x) = 5 \cos x + 3 \sin x \][/tex]
Applying the product rule:
[tex]\[ g'(x) = u'v + uv' \][/tex]
[tex]\[ g'(x) = 4 x^3 (5 \sin x - 3 \cos x) + x^4 (5 \cos x + 3 \sin x) \][/tex]
Simplify:
[tex]\[ g'(x) = 4 x^3 (5 \sin x - 3 \cos x) + x^4 (5 \cos x + 3 \sin x) \][/tex]
### Problem 8: Differentiate [tex]\(\frac{\sqrt{x} + 1}{\sqrt{x} - 1}\)[/tex]
Given the function:
[tex]\[ h(x) = \frac{\sqrt{x} + 1}{\sqrt{x} - 1}\][/tex]
To differentiate the quotient of two functions, we use the quotient rule:
[tex]\[ \left( \frac{u}{v} \right)' = \frac{u'v - uv'}{v^2} \][/tex]
Let:
[tex]\[ u = \sqrt{x} + 1 \][/tex]
[tex]\[ v = \sqrt{x} - 1 \][/tex]
Find the derivatives of [tex]\( u \)[/tex] and [tex]\( v \)[/tex]:
[tex]\[ u' = \frac{d}{dx} (\sqrt{x} + 1) = \frac{1}{2\sqrt{x}} \][/tex]
[tex]\[ v' = \frac{d}{dx} (\sqrt{x} - 1) = \frac{1}{2\sqrt{x}} \][/tex]
Applying the quotient rule:
[tex]\[ h'(x) = \frac{u'v - uv'}{v^2} \][/tex]
[tex]\[ h'(x) = \frac{\left(\frac{1}{2\sqrt{x}}\right)(\sqrt{x} - 1) - (\sqrt{x} + 1)\left(\frac{1}{2\sqrt{x}}\right)}{(\sqrt{x} - 1)^2} \][/tex]
Simplify:
[tex]\[ h'(x) = \frac{\frac{\sqrt{x} - 1 - \sqrt{x} - 1}{2\sqrt{x}}}{(\sqrt{x} - 1)^2} \][/tex]
[tex]\[ h'(x) = \frac{-2}{2\sqrt{x} (\sqrt{x} - 1)^2} \][/tex]
[tex]\[ h'(x) = \frac{-1}{\sqrt{x} (\sqrt{x} - 1)^2} \][/tex]
So the final derivative is:
[tex]\[ h'(x) = \frac{1}{2\sqrt{x}(\sqrt{x} - 1)} - \frac{\sqrt{x} + 1}{2\sqrt{x}(\sqrt{x} - 1)^2} \][/tex]
Thus, we have:
1. [tex]\((8 x - 7) \sec x + (4 x^2 - 7 x + 5) \sec x \tan x\)[/tex]
2. [tex]\(x^4 (3 \sin x + 5 \cos x) + 4 x^3 (5 \sin x - 3 \cos x)\)[/tex]
3. [tex]\(\frac{1}{2 \sqrt{x} (\sqrt{x} - 1)} - \frac{\sqrt{x} + 1}{2 \sqrt{x} (\sqrt{x} - 1)^2}\)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.